A Preliminary Study on Rainfall Interception Loss and Water Yield Analysis on Arabica Coffee Plants in Central Aceh Regency, Indonesia - Alfiansyah Yulianur BC; Maimun Rizalihadi; Reza Benara (Aceh International Journal of Science and Technology, 2012)
Abstract - Rainfall interception loss from plants or trees can reduce a net rainfall as source of water yield. The amount of rainfall interception loss depends on kinds of plants and hydro-meteorological characteristics. Therefore, it is important to study rainfall interception loss such as from Arabica Coffee plantation which is as main agricultural commodity for Central Aceh Regency. In this study, rainfall interception loss from Arabica Coffee plants was studied in Kebet Village of Central Aceh Regency, Indonesia from January 20 to March 9, 2011. Arabica coffee plants used in this study was 15 years old, height of 1.5 m and canopy of 4.567 m2. Rainfall interception loss was determined based on water balance approach of daily rainfall, throughfall, and stemflow data. Empirical regression equation between rainfall interception loss and rainfall were adopted as a model to estimate rainfall interception loss from Arabica Coffee plantation, which the coefficient of correlation, r is 0.98. In water yield analysis, this formula was applied and founded that Arabica Coffee plants intercept 76% of annual rainfall or it leaved over annual net rainfall 24% of annual rainfall. Using this net rainfall, water yield produced from Paya Bener River which is the catchment area covered by Arabica Coffee plantation was analyzed in a planning of water supply project for water needs domestic of 3 sub-districts in Central Aceh Regency. Based on increasing population until year of 2025, the results showed that the water yield will be not enough from year of 2015. However, if the catchment area is covered by forest, the water yield is still enough until year of 2025